Reformulation of Supervision of The Constitutional Court in Carrying Out Its Functions as Judicial Power - Zaman, Nurus (Trunojoyo Madura University, 2024)
In this research, two issues will be discussed. First, the institutional position of the Constitutional Court and the Supreme Court, which are both regulated in the 1945 Constitution. Second, is it conceptually justified for the Constitutional Court to refuse external supervision like the Supreme Court. This research uses doctrinal normative legal research in collaboration with reform-oriented research methods. The results obtained in this research are as follows. First, the Constitutional Court and the Supreme Court institutionally have the same level; both have the same judicial authority to uphold law and justice. The Constitutional Court and the Supreme Court have the same basis for constitutionality, which is regulated in Article 24, paragraph (1) and paragraph (2) of the 1945 Constitution. The difference between the Constitutional Court and the Supreme Court lies in the scope of their powers. Second, the 1945 Constitution does not regulate the supervision of the Constitutional Court. However, the Constitutional Court and the Supreme Court are both regulated in the 1945 Constitution and have the same orientation, that is, to law and justice enforcement, so conceptually, there is no reason for the Constitutional Court to refuse external supervision like the Supreme Court.